Comparative analysis of lists of ecosystem services classified by function. (9th July 2019) - Bouredji, Aicha
Functional classification of ecosystem services is a very popular method, originated in the International Millennium Ecosystem Assessment Report. Other organisations have adopted this approach and have developed it by deploying it in their sustainable development strategies. These alternations prompted demands for appropriate public policies. Thus, the problem of environmental quantification appeared because it requires finely cohesive tools. To examine the compatibility of all the lists of ecosystem services, this paper proposes an inspection of the classifications proposed by eight global organisations and a comparative analysis of their rankings. This makes it possible to check whether it would be relevant to rely on these classifications for quantification. Through a thorough examination method, the compositions will be processed and enhanced. The results of this work will provide a theoretical framework as a tool to help environmental assessment. It will bring together a fixed set of services that helps implement a concrete application.